(untitled) (Journal of Libya for geographical studies, 2023)
The use of remote sensing and geographic information systems in monitoring and controlling the change in vegetation cover is important in preserving this resource from extinction due to some factors, foremost of which is the increase in population and the consequent increase in demand for urbanization, which leads to urban sprawl towards lands near the urban mass, which are often natural vegetation covers that were like natural plants or human such as lands allocated for agriculture. The study aims to detect the change in the area of vegetation cover due to the monitoring of the vegetation green index NDVI in the Sirte region by using satellite images Landsat 7 for the year 2003 and Landsat 8 for the years 2013 and 2023, analyzing them and deducing the area of change in them. The study found a change in the area of vegetation cover in the Sirte region from 2003 to 2023, where the area of vegetation cover decreased from 31.1% in 2003 to 21.4% in 2013 and then began to increase to